Karta Kamchatskago zaliva sostavlena po glazomi︠e︡rnoĭ sʺemki︠e︡ i promi︠e︡ru Shkhipera shkhuny "Storozhʺ" F. Gekʺ vʺ 1900 g. / Chertilʺ khimich. tushʹi︠u︡ M. Posisi︠e︡evʺ - Russia. Glavnoe gidrograficheskoe upravlenīe (Sankt-Peterburg : Morskoe ministerstvo, Glavnoe gidrograficheskoe upravlenīe; [Санкт-Петербург] : Морское министерство, Главное гидрографическое управленіе, 1902)
Relief shown by form lines. Depths shown by soundings.; Main title translation: Map of the Gulf of Kamchatka compiled from the survey of the schooner "Storozh" under F. Höök (Fridolf Höök) in 1900.; Top margin title translation: Bering Sea, eastern shore of the Kamchatka peninsula.; "Masshtabʺ 5045 s. ili 5,75 m. vʺ d." = Scale 5045 fathoms or 5.75 miles in 1 inch.; Greenwich meridian.; "No. 569" -- bottom right margins Color; 1:400,000